Forest Recreational Services in the Face of COVID-19 Pandemic Stress - Bamwesigye, Dastan; Fialová, Jitka; Kupec, Petr; Łukaszkiewicz, Jan; Fortuna-Antoszkiewicz, Beata (Land (Basel), 2021)
Forest ecosystems provide numerous services and benefits to both humans and biodiversity. Similarly, urban forests services play a vital role by providing urban dwellers with recreational and leisure space, mental health relief, and meditation. In the wake of the COVID-19 epidemic, many people living in the urban areas could benefit from the forest and park recreational services to relieve psychological stress due to lockdown rules. The study examined existing literature simultaneously; however, very few studies have presented the relationships between forest services’ role on COVID-19 stress relief. Furthermore, we examined forest visitors’ frequency at the Training Forest Enterprise (TFE) Masaryk Forest Křtiny in the outskirts of Brno City in the Czech Republic. The study collected data using a TRAFx infrared trail counter before the pandemic (2015–2018) and during the COVID-19 period (2021). As in other studies of the subject, we observed an increasing trend in forest visits during the COVID-19 lockdown in 2021, compared to the same months before the pandemic in 2016 and 2017. We recommend further research to focus on scientific analysis of the relationship between forest ecosystem services and COVID-19 stress and mental health. Moreover, given the spike in visitors during the COVID-19 lockdown in 2021 in March and April, our data provide evidence regarding the role of nature for relieving stress and supporting mental and physical health. Policy, decision-makers and medical advisors could use such data and study to guide future lockdowns and pandemic situations regarding nature and forest recreational use and importance.